2003
DOI: 10.1016/s0168-6496(03)00009-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and distribution of extra-slow-growing Bradyrhizobium japonicum harboring high copy numbers of RSα, RSβ and IS1631

Abstract: We previously reported that extra-slow-growing Bradyrhizobium japonicum isolates obtained from three field sites in Japan, designated as HRS (highly reiterated sequence-possessing) strains, have high copy numbers of the insertion sequences RSalpha and RSbeta. When strain collections in the USA, Japan, Korea, Thailand and China were examined by Southern hybridization using RSalpha, RSbeta and IS1631 as probes, HRS strains were found in the Japanese, Chinese, and American collections, but not in the Korean and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 36 publications
0
49
0
2
Order By: Relevance
“…The tree based on the 16S rRNA gene divided the B. japonicum strains into two main clusters, BJ1 and BJ2, as described earlier (Sameshima et al, 2003;Sameshima-Saito et al, 2006) (Figure 3a). B. japonicum strains belonging to the two genome types 110 and 122, as defined by the CGH profile (Figures 1 and 2), still formed a single clade, BJ1 (Figure 3a).…”
Section: Conditions and Presentation Of Cgh Analysismentioning
confidence: 74%
“…The tree based on the 16S rRNA gene divided the B. japonicum strains into two main clusters, BJ1 and BJ2, as described earlier (Sameshima et al, 2003;Sameshima-Saito et al, 2006) (Figure 3a). B. japonicum strains belonging to the two genome types 110 and 122, as defined by the CGH profile (Figures 1 and 2), still formed a single clade, BJ1 (Figure 3a).…”
Section: Conditions and Presentation Of Cgh Analysismentioning
confidence: 74%
“…Previously, these core house-keeping loci were used in comparative analysis in the taxonomic characterization of rhizobia. 23,[47][48][49][50][51] It has been reported that these protein coding-loci are unlinked in the genome and that they provide independent genealogies for the inference of a reliable phylogenetic tree. 52,53) Sequences of our target house-keeping genes for all the strains were not available in the Genbank, which is why we could not use the same set of strains to construct all the phylogenetic trees.…”
Section: Strain Ek05mentioning
confidence: 99%
“…This polymorphism is probably due to truncation of the processes of anaerobic nitrate respiration (31). It has been shown that indigenous populations of soybean bradyrhizobia show significant field site variation in terms of DNA fingerprints according to insertion sequences, species level, and hydrogen uptake phenotype and genotype (7,16,17,21). Similarly, we wanted to determine whether the denitrification patterns of indigenous populations of soybean bradyrhizobia differed in accordance with their field sites.…”
mentioning
confidence: 99%
“…Ϫ, the isolate evolved no 30 c Genotype and phenotype of uptake hydrogenase (16,18). d HRS, highly reiterated sequence-possessing strains carrying high copy numbers of insertion sequences (9,15,18,21).…”
mentioning
confidence: 99%